The Effect of Think Talk Write Strategy Toward Students’ Writing Skill - Fuadiyah, Muniyatul; Sukendra, Irmala; Moddies Swara, Marrieta (Foremost Journal, 2025)
The experimental research was aimed to find out whether there was significant effect of students writing skill after taught by using Think Talk Write strategy on the tenth grade of SMAN 15 Kota Tangerang. This research was conducted in two classes; the experimental class (X IPS 5) consisted of 37 students and control class (X IPS 3) consisted of 36 students as sample. The data was gained by pre-test and post-test, it was found that the mean of pre-test in experimental class was 69.81 and the post-test was 76.49. It meant that there was significant effect of students writing skill after taught by using Think Talk Write strategy on the tenth grade of SMAN 15 Kota Tangerang. However, based on the t-test formula it was obtained that was -0.579 and was -1.667. It indicated that was accepted and was rejected because was higher than (-0.579 -1.667). Based on the result of t-test, the writer concluded that there was no significant difference between the writing skill improvement of students who taught by using Think Talk Write and who taught by using Discovery Learning.